2017
DOI: 10.1017/s1368980017002129
|View full text |Cite
|
Sign up to set email alerts
|

Energy contribution of NOVA food groups and sociodemographic determinants of ultra-processed food consumption in the Mexican population

Abstract: In 2012, about 30 % of energy in the Mexican diet came from UPF. Our results showed that younger ages, urbanization, living in the North region, high socio-economic status and high head of household educational level are sociodemographic factors related to higher consumption of UPF in Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
153
2
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(190 citation statements)
references
References 31 publications
11
153
2
24
Order By: Relevance
“…the quality of the diet increases as income increases] and the poor spend a great proportion of their income on food) shows a positive obesity reviews correlation (in fact a disproportionate increase) between income increase and the share of the diet from fruits, vegetables, meats, fish, dairy and fats; Bennett's law has been borne out in empirical studies in LAC (116). Studies also show a correlation between income and the purchase of processed food in LAC (75,(117)(118)(119)(120).…”
Section: Income Growthmentioning
confidence: 98%
“…the quality of the diet increases as income increases] and the poor spend a great proportion of their income on food) shows a positive obesity reviews correlation (in fact a disproportionate increase) between income increase and the share of the diet from fruits, vegetables, meats, fish, dairy and fats; Bennett's law has been borne out in empirical studies in LAC (116). Studies also show a correlation between income and the purchase of processed food in LAC (75,(117)(118)(119)(120).…”
Section: Income Growthmentioning
confidence: 98%
“…UPFD already correspond to more than 50% of total energy intake in high income countries, such as the United States and Canada, and their consumption is increasing rapidly in middle‐income countries . Consumption of UPFD has been associated with unhealthy dietary patterns and with overweight and obesity in studies conducted in the United Kingdom, United States, Canada, Chile, Colombia, and Brazil .…”
Section: Introductionmentioning
confidence: 99%
“…15 UPFD already correspond to more than 50% of total energy intake in high income countries, such as the United States 16,17 and Canada, 18 and their consumption is increasing rapidly in middleincome countries. [19][20][21][22] Consumption of UPFD has been associated with unhealthy dietary patterns [23][24][25][26][27][28][29][30] and with overweight and obesity in studies conducted in the United Kingdom, United States, Canada, Chile, Colombia, and Brazil. 13,[31][32][33][34][35][36] A longitudinal study in Latin America, that included 13 countries, found a positive, strong, and statistically significant association between annual changes in sales per capita of UPFD and annual changes in mean BMI after controlling for confounding factors.…”
mentioning
confidence: 99%
“…Pizzas, sodas and juices were among the most consumed products among these age groups [12]. In low-and middle-income countries, the consumption of UPF is lower (18-35%), but young children are still their earliest adopters and their largest consumers [3,14,15].…”
mentioning
confidence: 99%